(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
India is a significant market for the Fast-Moving Consumer Goods (FMCG) businesses because of its vast population. There are numerous large and small companies currently operating and having considerable impact on the industry. The current paper has been prepared to evaluate the development of Ayurveda brand so quickly in the industry, it is obvious that this trip of Ayurveda was not an easy job as Ayurveda being very much new. But the method of positioning, branding and eventually strategy to build a confidence and trust in customer make a difference and Ayurveda’s market share was so fast that it has over take many goods of renowned brand in only 2 to 3 years and emerge as a market leader. The marketing strategy of Swami Ramdev was executed so beautifully in market and his major formula was “swadeshi” that has created a magic and attract a good number of consumers along with a good number of raw material supplier’s i.e., Indian farmer. There is a need to promote the indigenous grown and produced goods.